SEM ANALYSIS OF THE INFLUENCE OF CONVENIENCE, PRODUCT QUALITY, PRICE AND PROMOTION ON PURCHASE DECISIONS AT SHOPEE BERKAH - Amini, Salisa; Muda, Iskandar; Soemitra, Andri; Yusrizal; Ismail (JURNAL ILMIAH EDUNOMIKA, 2025)
This research is motivated by the rapid development of e-commerce in Indonesia, especially the Shopee platform, which is one of the largest marketplaces in Southeast Asia. In a rapidly evolving digital ecosystem, it's important to identify the factors that influence consumer purchasing decisions. The purpose of this study is to analyze the influence of convenience, product quality, price, and promotion on purchase decisions at Shopee Berkah using the Structural Equation Modeling (SEM) approach. The research method used was quantitative with purposive sampling technique, involving 100 UINSU student respondents who had shopped at Shopee Berkah. Data collection was carried out through the distribution of online questionnaires, and data analysis using Partial Least Squares (PLS) with the help of SmartPLS software. The results showed that the price and quality of the product had a positive and significant effect on the purchase decision, with t-statistical values of 13.005 and 3.151 respectively (p-value < 0.05). Meanwhile, the convenience and promotion variables did not show a significant influence with p-values of 0.306 and 0.937, respectively. The research model was able to explain 84.8% of the variation in consumer purchasing decisions. In conclusion, in the context of Shopee Berkah, price and product quality are the main factors that affect consumer purchase decisions, while ease of use and promotional strategies have not shown a significant influence.